MSMEs Management Strategy Impact in the Pandemic Period of Sinarsari Village, Bogor - Putri Aulia, Mega; Jaelani, Alan (Universitas Ibn Khaldun, 2022)
Currently, the economy in Indonesia is being hit by the ups and downs of market prices due to the worsening COVID-19 situation. This has a fairly strong impact for entrepreneurs in Indonesia on unstable sales, especially micro, small and medium enterprises (MSMEs). Where small entrepreneurs have to rotate the strategy so that the processing until the sale continues. As experienced by small entrepreneurs from the village of Sinarsari Bogor who have to rotate their small business management strategy, namely drinks with natural herbal drinks (Bandrek, red ginger, and bajigur) to keep going. The impacts experienced include the price of materials, sales, enthusiasts to the workforce which continues to decrease. Therefore, this article will discuss the management strategies used to the impacts and challenges that occurred during the pandemic on the management of MSMEs.